Peningkatan Kepercayaan Diri Korban Bullying Melalui Layanan Konseling Kelompok Dengan Teknik Assertive Training - Wardani, Silvia Yula; Mahmudi, Ibnu; Trisnani, Rischa Pramudia (Universitas Muria Kudus, 2020)
The purpose of this reseach to determine the level of confidence of victims of bullying and the effectiveness of group counseling services with assertive training techniques. The sampling technique was purposive sampling, where students were victims of bullying. The method to data collection in this research was through a questionnaire of self-confidence of victims of bullying in SMP Negeri 8 Madiun. This research uses a quantitative approach, precisely research experiments. Data analysis techniques used t-test to determine the differences before being treated with peer counseling and after being treated with group counseling with assertive training techniques. The results showed a difference in scores between before and after treatment was given. SPSS test results using t test showed a sign value of 0.00 the conclusion of this study is group counseling services with effective asertive training techniques to increase the confidence of bullying victims.